2014
DOI: 10.1155/2014/129259
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Profiling of the Peripheral Blood Mononuclear Cells Proteome for Clinical Blood Proteomics

Abstract: Peripheral blood mononuclear cells (PBMCs) are an easy accessible cellular part of the blood organ and, along with platelets, represent the only site of active gene expression in blood. These cells undergo immunophenotypic changes in various diseases and represent a peripheral source of monitoring gene expression and posttranslational modifications relevant to many diseases. Little is known about the source of many blood proteins and we hypothesise that release from PBMCs through active and passive mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…Intracellular synthesis of a partial FVIII and of the FVIII B proteins has been reported in PBMCs and liver tissue from intron-22-inversion HA subjects. 62,63 However, recent proteomics studies have not confirmed FVIII or FVIII B expression in PBMCs or in thymus peptides associated with HLA-DR. 64,65 The isolation reported herein of FVIII-C2-specific T-effector clones and lines from a severe HA subject whose F8 mutation did not affect the F8B region demonstrates directly that the FVIII-C2 domain is a target for T cells in HA subjects and thereby argues against widespread central tolerance to this domain.…”
Section: Org Frommentioning
confidence: 73%
“…Intracellular synthesis of a partial FVIII and of the FVIII B proteins has been reported in PBMCs and liver tissue from intron-22-inversion HA subjects. 62,63 However, recent proteomics studies have not confirmed FVIII or FVIII B expression in PBMCs or in thymus peptides associated with HLA-DR. 64,65 The isolation reported herein of FVIII-C2-specific T-effector clones and lines from a severe HA subject whose F8 mutation did not affect the F8B region demonstrates directly that the FVIII-C2 domain is a target for T cells in HA subjects and thereby argues against widespread central tolerance to this domain.…”
Section: Org Frommentioning
confidence: 73%
“…These cells suffer from DNA lesions in CAD patients but little is known about its underlying molecular events. Furthermore, their availability makes them a suitable source of noninvasive predictive biomarkers in clinical studies [20].…”
Section: Discussionmentioning
confidence: 99%
“…PBMCs contain different cell types including, T, B, natural killer (NK) and dendritic cells. These cells play important roles in the immune system monitoring, and immune-relevant events [9]. These cells undergo immunophenotypic changes in various diseases and represent a peripheral source of monitoring gene expression and posttranslational modifications relevant to many diseases.…”
Section: Introductionmentioning
confidence: 99%